Adaptation to Motherhood and Its Influential Factors in the First Year Postpartum in Iranian Primiparous - Hamzehgardeshi Z; Shahhosseini Z; Moosazadeh M; rezaeekalantari R; Hajizade-valokolaee M (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Postpartum is a significant transition period for women and could be markedly stressful. Postpartum stress is a well-established risk factor for poor parenting practices and inadequate mother-infant interaction. Objectives: The present study aimed to assess adaptation to motherhood and its influential factors in the first year postpartum in Iranian women. Methods: This cross-sectional study was performed in an urban area in the north of Iran. Inclusion criteria were age of more than 18 years, primiparous women, having healthy children in less than one year postpartum, Persian literacy, and willingness to participate in the research. Ill and disabled women, those with a history of depression, and high-risk pregnancies were excluded from the study. Convenience sampling was employed in seven health centers, and 536 subjects were selected. Data were collected using the scale of the experiences of Iranian first-time mothers in maternal role adaptation and demographic questionnaires. Data analysis was performed using descriptive statistics and regression and ordinal logistic regression. Results: None of the women had poor adaptation to motherhood. In addition, 2.6% of the subjects had average adaptation, 78.8% had good adaptation, and 18.6% had excellent adaptation. According to the logistic regression results, favorable economic status increased the possibility of appropriate adaptation by twice (OR=2.03; CI: 1.3-3.004; P<0.001). Conclusion: Provision of proper counseling services requires the recognition of the influential factors in adaptation to motherhood. According to the results, adaption of women to motherhood in the first year postpartum largely depends on the economic support of the mother and infant.